ANALISIS TINGKAT PENDAPATAN BUAH NAGA PADA KELOMPOK INFORMASI MASYARAKAT (KIM) MEKAR KARYA ARSO XIV KABUPATEN KEEROM - Daniel A. Dawan (Universitas Nahdlatul Ulama Sidoarjo, 2020)
Analysis of Dragon Fruit Income Level in the Mekar Karya Arso XIV Community Information Group (KIM) Keerom Regency. The purpose of this research is to provide useful information for investors who are interested in developing or investing in dragon fruit farming in Mekar Karya, Arso XIV, Keerom Regency. This research uses the field study method (field study). Library research (library research) to get the results of the objectives of this study. So the research results show that by using the income statement, analysis of R / C Ratio, and BEP to determine the level of income dragon fruit farmers. From the calculation of the respondent's income, the net income obtained is around Rp. 12,766,944 and has a value of 1.684 While the value of BEP (Rp) shows that the KIM Mekar Karya Arso XIV dragon fruit farming is feasible to be cultivated. factors that can influence in the agricultural business of KIM Mekar Karya in Arso XIV Skanto District, Keerom Regency, namely: 1). Climate, 2). Disease / Pests 3). Skill 4). Selling price